Modification of Fluorescent Photoinduced Electron Transfer (PET) Sensors/Switches To Produce Molecular Photo‐Ionic Triode Action1. (26th February 2014) - Huxley, Allen J. M.; Schroeder, Marc; Nimal Gunaratne, H. Q.; Prasanna de Silva, A.
Abstract The fluorophore‐spacer1‐receptor1‐spacer2‐receptor2 system (where receptor2 alone is photoredox‐inactive) shows ionically tunable proton‐induced fluorescence off‐on switching, which is reminiscent of thermionic triode behavior. This also represents a new extension to modular switch systems based on photoinduced electron transfer (PET) towards the emulation of analogue electronic devices.